„Happy as the Jew in Paris”: the Artists of the School of Paris from the Belarus, Lithuania, Latvia - Lisov, Alexander (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
This article examines the genesis of the relations of artists of the School of Paris to the problem of Jewish national art. The Paris art scene opened to Jewish artists an opportunity of free creative activity, and, at the same time, it raised a question about the content of the concept of “Jewish art.” In the community of exiles in Paris there was formed the different views on Jewish theme in art, on the problem of national stylistic identity. The author specifies some contradictions in the content of these definitions, which legitimacy of use in modern art criticism isn’t in question any more. The term “School of Paris” doesn’t receive the accurate scientific development until today. This name contains a geographical reference, which, however, doesn’t give any criterion in defining the circle of the names of participants. Most often, the School is associated with an international range of artists established in Paris in the 1910-ies – 20-ies. In the circle of artists of the School of Paris, there predominate numerically the names from the overpopulated by Jews Ukrainian, Lithuanian, Belarusian provinces of the Russian Empire. It was not just those who simply lived in Paris. They were the ones who tried to take root into the local art environment. They were attracted not only by the particular situation of Paris, the cultural and artistic capital, but also by the civil liberties to which they could have access in France, in contrast to the countries of the Central and Eastern Europe. Their attempts to adapt in Paris were not always successful. The question of the meaning of the terms “Jewish art”, “Jewish artist” is relevant today as it was a hundred years ago. Attitude towards the Jewry and the national perspective in art was ambiguous among the Parisian Jewish artists. A number of Jews, members of the School of Paris, distanced himself from the Jewry. Among them could be called O. Zadkine and Ch. Soutine. They often invented and created for themselves new versions instead of their real autobiographies. For them the creative freedom was the freedom from the Jewry. They deliberately refused from Jewish themes in their art. Artists such as Chagall, recognized and accentuated their relation to the Jewry, including their artistic expression. However, they were far from the interest to the theoretical interpretation of the idea of National art. Finally, the third way of a Jewish artist assumed to search for meaning inside the concept of “Jewish art” and of “Jewish” art form. This is typical, for example, for the artists of the Parisian group called “Mahmadim.” The group was united around the magazine of the same name. Paris opened to Jewish artists a freedom of the art expression. The “Jewish” theme was the first step to this freedom. But now it was not already a Biblical theme which at the initial stage of the formation of Jewish Art substituted a Jewish theme and was treated as “Jewish”. From these new positions the Jewish artists turned to modernity, to genre, to everyday, recognizable life of the shtetl, the town the Pale. This was a step in the direction to a truly Jewish art. It created a necessity of the formulation of the problem of National art, the content of which was discussed actively. The search of a National style turned Jewish artists to European innovations in the plastic language. The freedom of styling, innovation, enriched the traditional, folk forms of Jewish art. But the expected National art could be mature only in conjunction with the National ideology, could be formed in a community, and this situation at the same time threatened the creative identity of an artist.